Reproducibility of airway dimensions and tongue and hyoid positions on lateral cephalograms - (:unkn) unknown (MOSBY-ELSEVIER, 2005)
Introduction: The aim of this study was to evaluate the reproducibility of airway dimensions and tongue and hyoid positions on lateral cephalometric radiographs. Methods: Three lateral cephalograms each of 30 patients were obtained in natural head positions at 30-minute intervals. Twelve measurements, including pharyngeal airway dimensions and tongue and hyoid positions, were taken. The relationships between 3 sets of measurements were evaluated by using repeated analysis of variance, Dahlberg's method error formula, and correlation coefficient. Results: No statistically significant differences were found between the 3 sets of measurements with the repeated analysis of variance (P > .05). Correlation coefficient values ranged between 0.964 (vertical position of the hyoid) and 0.683 (hypopharyngeal airway width). The average method error was 1.22 mm. Conclusions: The results suggest that airway dimension and tongue- and hyoid-position measurements are highly reproducible on natural-head-position cephalograms.
Keywords: NATURAL HEAD POSITION; NASAL AIRWAY; INCLINOMETER; BONE